Evaluation of heavy chain C‐terminal deletions on productivity and product quality of monoclonal antibodies in Chinese hamster ovary (CHO) cells. (24th March 2017) - Hu, Zhilan; Tang, Danming; Misaghi, Shahram; Jiang, Guoying; Yu, Christopher; Yim, Mandy; Shaw, David; Snedecor, Brad; Laird, Michael W.; Shen, Amy
Abstract : Monoclonal antibodies (mAbs) have been well established as potent therapeutic agents and are used to treat many different diseases. During cell culture production, antibody charge variants can be generated by cleavage of heavy chain (HC) C‐terminal lysine and proline amidation. Differences in levels of charge variants during manufacturing process changes make it challenging to demonstrate process comparability. In order to reduce heterogeneity and achieve consistent product quality, we generated and expressed antibodies with deletion of either HC C‐terminal lysine (‐K) or lysine and glycine (‐GK). Interestingly, clones that express antibodies lacking HC C‐terminal lysine (‐K) had considerably lower specific productivities compared to clones that expressed either wild type antibodies (WT) or antibodies lacking HC glycine and lysine (‐GK). While no measurable differences in antibody HC and LC mRNA levels, glycosylation and secretion were observed, our analysis suggests that the lower specific productivity of clones expressing antibody lacking HC C‐terminal lysine was due to slower antibody HC synthesis and faster antibody degradation. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:786–794, 2017